GB energy networks: experts' views on future pathways and multi-vector energy networks approach - Oduro, Richard A.; Taylor, Peter G. (Frontiers in Sustainable Energy Policy, 2025)
The decarbonization of energy systems poses significant challenges to energy networks due to the introduction of new energy vectors and changes in the pattern of energy demand. However, this is currently an under-researched area. This paper addresses a gap in the literature by drawing on the socio-technological transitions and multi-system interactions literature to explore the views of experts from industry, academia and other sectors about the challenges facing UK energy networks and the possible solutions, including taking a more wholistic approach to the planning and operation of different networks. Using these frameworks, we have demonstrated that systems can be deliberately integrated to interact and solve particular system challenges, and have identified the nature of these interactions. The empirical results identify areas of consensus and disagreement about the future development of network infrastructure and regulation. They also highlight how government policy responds to the challenges and opportunities presented by the UK climate targets. The findings show widespread agreement that the UK energy system will become more electrified and decentralized as it incorporates more renewable energy. However, the role of gaseous fuels in the energy system is more uncertain, with some experts seeing a move from natural gas to hydrogen as being key to maintaining the security of supply, while others see little or no role for hydrogen. There is also widespread agreement that the regulatory structure should change to address the challenges facing energy networks with much less agreement on whether this could happen quickly enough. Recent developments indicate the UK Government recognizes the need for regulatory change, but it is premature to foresee their success in helping networks be a driver of, rather than a barrier to, a net-zero energy system.